Serological Surveillance of Rabies in Free-Range and Captive Common Vampire Bats Desmodus rotundus - Megid, Jane; Benavides Tala, Julio Andre; Belaz Silva, Laís Dário; Castro Castro, Fernando Favian; Ribeiro, Bruna Letícia Devidé; Appolinário, Camila Michele; Katz, Iana Suly Santos; Scheffer, Karin Corrêa; Silva, Sandriana Ramos; Rosa, Adriana Ruckert; Barone, Gisely Toledo; Alves Martorelli, Luzia Fátima; et al. (Frontiers in Veterinary Science, 2021)
In this study, we took advantage of recent outbreaks of VBR among livestock in the Sao Paulo region of Brazil to test whether seroprevalence in Desmodus rotundus reflects the incidence of rabies in nearby livestock populations.